Health risks associated with high waist circumference: a systematic review - Darsini; Hamidah; Hari Basuki Notobroto; Eko Agus Cahyono (SAGE Publishing, 2020)
Obesity is a health disorder characterized by an increase in body weight, measured by waist circumference. High waist circumference is linked to potential development of non-communicable diseases. A systematic review study was used to explore health risks of high waist circumference through Google Scholar, Science Direct, Pubmed, and Proquest. Findings show that high waist circumference increased the risks of developing hypertension, type 2 diabetes mellitus, hypercholesterolemia, joint pain, low back pain, and hyperuricemia. It is recommended that government increase their role in raising public awareness to maintain healthy lifestyle.